2016
DOI: 10.1530/joe-15-0524
|View full text |Cite
|
Sign up to set email alerts
|

Cell density-dependent stimulation of PAI-1 and hyaluronan synthesis by TGF-β in orbital fibroblasts

Abstract: During the course of Graves’ orbitopathy (GO), orbital fibroblasts are exposed to factors that lead to proliferation and extracellular matrix (ECM) overproduction. Increased levels of tissue plasminogen activator inhibitor type 1 (PAI-1 (SERPINE1)) might promote the accumulation of ECM components. PAI-1 expression is regulated by cell density and various cytokines and growth factors including transforming growth factorβ(TGF-β). We examined the effects of increasing cell densities and TGF-β on orbital fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
(56 reference statements)
2
13
0
Order By: Relevance
“…18 We assume that the effect of 4-MU on transcription of HAS genes with very low expression levels is less consistent; HAS2 expression was 2 orders of magnitude higher than HAS1 and HAS3 in the studied cells, as we described earlier. 11 This theory is supported by our observation that significant downregulating effect of 4-MU on the expression of HAS1 was observed in TGF-β stimulated cells where HAS1 transcription is substantially higher (Fig. 6B).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…18 We assume that the effect of 4-MU on transcription of HAS genes with very low expression levels is less consistent; HAS2 expression was 2 orders of magnitude higher than HAS1 and HAS3 in the studied cells, as we described earlier. 11 This theory is supported by our observation that significant downregulating effect of 4-MU on the expression of HAS1 was observed in TGF-β stimulated cells where HAS1 transcription is substantially higher (Fig. 6B).…”
Section: Discussionsupporting
confidence: 71%
“…Human fibroblasts were cultured as described previously in detail. 11 The cells were studied between passages 2 and 8. For experiments, orbital and dermal fibroblasts (OFs and DFs) were plated in 24-well or 96-well plates, in confluent cell density (1.56 × 10 4 cells/cm 2 ) in M199 supplemented with 10% (v/v) FBS.…”
Section: Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the expression and secretion of inflammatory cytokines (IL-6, IL-8, TNF-α, and MCP-1) were increased after IL-1β stimulation. Additionally, the expression and secretion of fibrotic factors (HA, α-SMA, FN, and Col-1, and extracellular matrix 51 ) were increased after TGF-β1 stimulation in OFs. Although all of these mediators were decreased after treatment with Gyps.…”
Section: Discussionmentioning
confidence: 96%